Mutational Scanning of PCR Products by Subtractive Oligonucleotide Hybridization Analysis. (February 1999) - Nilsson, P.; Larsson, A.; Lundeberg, J.; Uhlén, M.; Nygren, P.-Å.
Here, we describe a new approach for mutational scanning of PCR products through hybridization analysis between complementary oligonucleotides. Sets of overlapping probe oligonucleotides complementary to wild-type (WT) sequence are hybridized to microbead-immobilized PCR products under solution-like conditions. Mismatch-hybridization situations between a mutant sample and probe oligonucleotides result in higher remaining concentrations in solution of involved probe oligonucleotides. Post-hybridization supernatants are subsequently analyzed for their probe oligonucleotide compositions using surface plasmon resonance-based biosensor technology. Relative remaining probe oligonucleotide concentrations are monitored in real-time through hybridization analysis between probe oligonucleotides and their corresponding sensor-chip immobilized complementary counterparts. This allows for the construction of composition diagrams revealing the existence and approximate location of a mutation within an investigated sample DNA sequence. Applied on PCR products derived from clinical samples of microdissected tumor biopsies, single mutations in exons 6 and 7 of the human p53 tumor-suppressor gene were successfully detected and approximately localized.